Determinants of indiscriminate antimicrobial use in commercial chicken farms in Bangladesh and their impact on food safety and public health - Mehedi Hasan; Tiasha Ali; A. K. M. Dawlat Khan; Monjurul Islam; Arif Khan; Abu Sayeed; Zulqarnine Ibne Noman; Abdullah Al Mamun; Shariful Islam; Mohammad Mahmudul Hassasn; Cameron E. F. Clark; Tahmina Shirin; et al. (Scientific Reports)
Abstract Antimicrobial resistance (AMR), associated with irrational antimicrobial use (AMU) poses a significant health threat to both humans and animals. Thus, our research determined AMU patterns and their associated factors in Bangladeshi chicken farms. We conducted a cross-sectional study in 340 commercial chicken farms comprising broilers (109), layers (109), and Sonali (122) farms in seven districts of Bangladesh from September to October 2021. Data were collected using in-person interviews with a pre-tested semi-structured questionnaire. Statistical analyses were performed, including descriptive statistics to understand farmer demographics and AMU practices, a Chi-square test to evaluate farmers’ knowledge, attitudes and practices (KAP), and logistic regression analysis to determine the factors associated with AMU. The findings indicated that 93.2% (317/340) farms administered at least one antimicrobial (AM) to chickens during the production cycle, with 67.0% of farmers used antimicrobials (AMs) in the 14 days before data collection. The usage of AMs was higher in meat-type chickens, such as broiler (78.0%) and Sonali (67.2%), in contrast to egg-type chickens, like layer (41.3%). The AMU practices were significantly associated with multiple factors, such as farming experience, poultry production type, knowledge gaps in proper AMU practices, the person managing the farm, reuse of left-over AMs, and compliance with veterinarians’ recommendations. We highlight the indiscriminate use of AMs that is occurring in poultry industry in Bangladesh, which could result in AM residues and resistance, posing detrimental consequences for public health. Farmers training on increasing their KAP regarding AMU to protect animal health, human health, and the ecosystem, is urgently needed.